2017
DOI: 10.1016/j.scitotenv.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of chronic fluoride exposure in groundwater in a highly exposed population

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 57 publications
0
26
2
1
Order By: Relevance
“…However, overall the evidence from this study shows that As contamination is not likely to be a widespread issue across this region and is more likely associated with particular geological settings, for example F and As hot-spots in the Rift Valley (e.g. Rango et al 2017).…”
Section: Discussionmentioning
confidence: 74%
“…However, overall the evidence from this study shows that As contamination is not likely to be a widespread issue across this region and is more likely associated with particular geological settings, for example F and As hot-spots in the Rift Valley (e.g. Rango et al 2017).…”
Section: Discussionmentioning
confidence: 74%
“…The highest fluoride concentration reported 2,800 mg/l in Lake Nakuru in Kenya (4). Like other African countries crossed by Rift Valley, fluoride is also a major health problem for communities using ground water sources in the Ethiopian Rift valley area (3,(10)(11)(12). Nearly 8 million people in the Ethiopian Rift Valley are drinking from high fluoride water sources (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in African countries, including Tanzania, Sudan, Nigeria and Kenya have found a high prevalence of dental fluorosis among populations that consume drinking water with high fluoride content (4,13,15). High fluoride concentration in ground water resulted high prevalence of dental fluorosis in the Ethiopian Rift Valley (7,11,12) which have lifelong health impacts ranged from loss of teeth to debilitating pain (7,16). About 13 million people also thought to be at risk of developing fluorosis in this region (3).…”
Section: Introductionmentioning
confidence: 99%
“…The highest fluoride concentration reported 2,800 mg/l in Lake Nakuru in Kenya (4). Like other African countries situated in Rift Valley, fluoride is also a major health problem for communities using ground water sources in the Ethiopian Rift valley area (3,(10)(11)(12). Nearly 8 million people in the Ethiopian Rift Valley are drinking from high fluoride water sources (7).…”
mentioning
confidence: 99%
“…Several studies in African countries, including Tanzania, Sudan, Nigeria and Kenya have found a high prevalence of dental fluorosis among populations that consume drinking water with high fluoride content (4,13,15). High fluoride concentration in ground water resulted high prevalence of dental fluorosis in the Ethiopian Rift Valley (7,11,12) which has lifelong health impacts ranged from loss of teeth to debilitating pain (7,16).…”
mentioning
confidence: 99%